Meat characteristics of buffaloes (Bubalus bub- alis) in two production systems and two slaugh- ter weights - David Hernández-Sánchez; René Rodríguez-Florentino; Luis A. de la Cruz-Cruz; Efrén Ramírez-Bribiesca; María M. Crosby Galván; Miguel Á. Mata-Espinosa; René Pinto-Ruiz (Revista Científica)
Under two production systems, this study evaluated carcass and meat characteristics of finished male buffaloes at 400 and 600 kg live weight (LW). Twenty-eight male buffaloes uncastrated of 216 ± 21.9 kg LW were used and were randomly distributed into four treatments (T): T1 and T2, grazing buffaloes (GB), slaughtered at 400 and 600 kg LW, respectively; T3 and T4, buffaloes in intensive system (IS), slaughtered at 400 and 600 kg LW, respectively. GB groups remained in a Brachiaria humidicola meadow (6.8% CP, 66.4% NDF, and 2 Mcal EM kg-1 DM) and were supplemented (32.02% CP, 25.19% NDF, and 2.8 Mcal ME kg-1 MS) at 1% of LW. The diet provided in the IS contained 14.22% CP, 44.25% NDF, and 2.7 Mcal ME kg-1 MS. The supplement’s nutrients for GB and the diet provided in IS were adjusted according to the change in the animals’ LW. The time to reach slaughter weight was 301, 368, 228, and 304 d for T1 to T4, respectively. After slaughter, the empty live weight (ELW= The filled green viscera were weighed, and later, they were washed with running water to remove the contenta and determine the empty weight) and cold carcass yield (CCY=Cold carcass weight/slaughter weight) were evaluated. Color (A Minolta colorimeter was used to record the values of *L, *a, and *b,) and pH was measured on the Longissimus dorsi muscle (24 h, and 7, 14, and 21 d); in addition to performing the proximal chemical analysis (moisture, crude protein, fat, and collagen), resistance to cutting and water retention capacity. A completely randomized design with a 2 x 2 factorial arrangement was used. The ELW of the buffaloes slaughtered at 400 kg did not vary (p> 0.05) between the GB or IS, nor did it vary between the groups slaughtered at 600 kg. However, the CCY of the animals sacrificed at 600 kg was higher in the IS than in the GB (54.06 b vs 57.97a). Meat from T4 had the highest pH values (p< 0.001; 5.81 c, 6.04 b , 6.08 b , 6.24a at 24 h, and 5.72 b , 5.93 b , 5.72 b and 6.13a at 7 days, T1 to T4, respectively). No differences (p> 0.05) were observed between moisture and protein content treatments. Nevertheless, fat content was higher (p< 0.001) in T2 and lower (p< 0.001) in T3 (2.28a vs 0.86 c), and collagen was higher (p< 0.01) in samples from GB (T1 and T2). The shear force was similar (p> 0.05) in the groups evaluated. Water retention capacity was higher (p< 0.05) in buffalos’ meat in IS (T3 and T4), and the lowest water retention was determined in animals kept grazing and sacrificed at 600 kg LW (T2). In conclusion, meat from buffaloes fed concentrates has lower (p<0.05) collagen and fat content, better color characteristics, pH, and water retention capacity, related to better meat quality. Due to the time needed to reach slaughter weight, it is recommended to slaughter buffaloes at 400 kg LW when fed in intensive systems to obtain better carcass and meat characteristics.